Adoption of Mobile Payment Approach Extended the UTAUT 2 - anna widayani (Relevance: Journal of Management and Business, 2021)
One of the most widely used mobile payment applications in Indonesia is LinkAja. This product has received official permission from Bank Indonesia as digital technology innovation in transactions. The purpose of this study was to determine the use of the LinkAja mobile payment with the UTAUT 2 approach. This type of research is explanatory research with a quantitative approach. This research analysis technique is descriptive and inferential using the Structural Equation Model-Partial Least Square (SEM-PLS). The population in this study was LinkAja users in Indonesia with a sample size of 249 respondents. The results showed that performance expectancy, facilitating conditions, hedonic motivation, price value, and habit have a positive and significant effect on behavior intention. Effort expectancy and social influence have a negative and significant effect on behavior intention. Behavioral Intention has a positive and significant effect on Actual Usage on the use of the LinkAja mobile payment.